VISA-FREE POLICY SUPPORTING ALTERNATIVES FOR TRAVELERS OF CHINA ORIGIN IN INDONESIA - Tony Mirwanto (Polteknik Imigrasi, 2019)
This study aims to provide an alternative in order to support the Visit Visa Free (BVK) policy issued by the Government of the Republic of Indonesia. The alternative is to require tourists, especially tourists from China who will use BVK facilities to use certain official Travel Agencies appointed by the Government of Indonesia. In this study discussed how the partnership relationship between the government of Indonesia and China in development in the field of tourism in Indonesia, and how alternative schemes are used in order to prevent violations of Residence Permits that are often carried out by tourists from China. This study uses a qualitative method. The results of the study concluded that: first, the partnership relationship in the tourism sector between the Indonesian government and China experienced significant progress, this was evidenced by the issuance of several policies that provided convenience for entering the Indonesian territory for tourists from China; and the two alternative schemes used by taking the concept of the implementation of Umrah which dispatched Indonesian citizens abroad, became the concept of bringing foreign tourists to Indonesia. The expectation is that the scheme can be stated in the form of legislation, so that the crime of Abuse of Residence Permit which has been dominated by Chinese Citizens can be reduced in number.